Complete Placenta Previa: Ultrasound Biometry and Surgical Outcomes - Alison C. Wortman; Stephanie L. Schaefer; Donald D. McIntire; Jeanne S. Sheffield; Diane M. Twickler (Thieme Medical Publishers, Inc., 2018)
Abstract Objective To evaluate the relationship between surgical outcomes and ultrasound measurement of placental extension beyond the cervical os in women with placenta previa. Study Design This is a retrospective cohort study of singleton pregnancies with placenta previa undergoing third-trimester ultrasound and delivering at our institution from 2002 through 2011. For study purposes, an investigator measured placental extension, defined as the placental distance from the internal os across the placenta continuing out to the lowest placental edge. If morbidly adherent placentation was suspected, women were excluded. Receiver operating characteristic (ROC) curves were developed for pertinent surgical outcomes, and multivariate analysis was performed to determine the placental extension with the best predictive discriminatory zone. Results In total, 157 women had placenta previa, ultrasound, and delivery data: 86 (55%) had a placental extension of <40 mm, and 71 (45%) had a placental extension of ≥40 mm. Women with placental extension of ≥40 mm had increased surgical time, blood loss > 2,000 mL, blood transfusion, and rate of peripartum hysterectomy. After multivariate analysis, only peripartum hysterectomy and surgical time > 90 minutes remained significant, p ≤ 0.05 and p ≤ 0.01, respectively. Conclusion In women with placenta previa, the placental extension ultrasound measurement of ≥40 mm is a predictor of adverse surgical outcomes.